Chemical Elements of the Periodic Table in Indigenous Language as a Teaching Resource for Contextualized Chemistry/Science Teaching - Wai Wai, Tewton; Carlos Castello, Kelly; Marne da Silva Araújo dos Santos, Virginia; Santos Barreto, Hosana Carolina; Santos, Ricardo Carvalho (Orbital: The Electronic Journal of Chemistry, 2025)
Roraima is the northernmost state in the Legal Amazon and the northernmost part of Brazil. Its population is over 600,000, of which approximately 15% are indigenous populations, the ethnic groups being Macuxi, Wapichana, Taurepang, Ingaricó, Patamona, Yanomami, Ye`kuana, Sapará, Waimiri Atroari and Waiwai. Indigenous populations in Brazil have few teaching materials that value the indigenous language and knowledge, as well as their relationship with science. The aim of this work is to develop contextualized, intercultural and interdisciplinary cards for teaching chemistry/science based on the identification of chemical elements of the Periodic Table found in the Holy Bible in the indigenous Waiwai language. To this end, we used applied research, with inductive reasoning, with exploratory and descriptive objectives for this study, with a qualitative approach using the documentary technique. The selection of documents was based on the Holy Bible translated into the Waiwai indigenous language, which resulted in 14 citations for sulfur (S), 86 for pehu (Fe), 35 for kobre (Cu), 10 for prata (Ag), 7 for estañu (Sn), 182 for ooru (Au) and 9 citations for xumbu (Pb). These were used in the construction of the teaching material. Through categorization, the data were decoded and interpreted. The educational product developed, the cards, is a teaching material for teaching chemistry/sciences that is contextualized and expresses the ethnic group's cultural and identity. In this sense, the production of cards seems to be an effective pedagogical resource for teaching chemistry/sciences in an intercultural context.